Global Rasdhul Qibla: The Probability of Four Times in A Year Study - Amin, Muhammad Faishol (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The global rashdul qibla commonly called istiwa' a'dzam occurs twice a year, 15/16 July and 27/28 May. On that date, the place that occurs during the day (illuminated by the Sun) can use the Sun's shadow to determine the direction of the qibla, because at that time the Sun is right above the Ka’ba. And for places where the night experiences (not illuminated by the sun), then you can use the rashdul qibla of the turning point of the Ka'ba, which is on January 13/14 and 28/29 November. In this study, the authors found the probability of rashdul qibla occurring four times a year somewhere. That is the combination of the rashdul qibla when the Sun is above the Ka’ba, and the rashdul qibla when the Sun is above the turning point of the Ka'ba. These places include Ambon, Namlea (Indonesia), Perth, Broome (Australia) and Tutuala (Timor Leste). Qibla rashdul July 15-16 and 27/28 May take place in the late evening, and qibla rashdul January 13-14 and 28/29 November occurs in the morning, after the sun rises.